2008
DOI: 10.1111/j.1747-4477.2007.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of the penetration of methylene blue dye in human radicular dentin using different methods of impregnation

Abstract: The purpose of the present study was to verity whether different conditions of contact with a dye solution would result in different levels of the impregnation by the marker agent in human radicular dentin. The root canals of 60 upper human canines were immersed in methylene blue dye (0.5%, pH 7.0) for 24 h under six different conditions: passive immersion; pre-agitation for 10 min using an endodontic ultrasound; pre-agitation for 10 min using a cleaning ultrasound; 25-mmHg vacuum for 10 min followed by passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…One reason for such a phenomenon might be the presence of air bubbles that can inhibit the penetration process (1,11). Also, it has been shown that the type of dye, methylene blue or fuchsine, or even the vacuum conditions don't change the amount of dye penetration (12,13). In the present study, we placed dye on top of the root end filling material to take advantage of gravity force.…”
Section: Discussionmentioning
confidence: 94%
“…One reason for such a phenomenon might be the presence of air bubbles that can inhibit the penetration process (1,11). Also, it has been shown that the type of dye, methylene blue or fuchsine, or even the vacuum conditions don't change the amount of dye penetration (12,13). In the present study, we placed dye on top of the root end filling material to take advantage of gravity force.…”
Section: Discussionmentioning
confidence: 94%
“…Yet, there have been disparities in these trials 7 have been conflicting. 8 In the existing study, SEM-a method of histological evaluation has been used to assess the root canal seal quality. Scanning Electron Microscope has greater resolution, improved interface magnification, and superior field depth, which has also been stated by Punithia and Shashikala.…”
Section: Discussionmentioning
confidence: 99%
“…In the gap between dentin and filling materials, methylene blue solution penetrates into dentin tubules easier than do filling materials. Therefore, dentin in contact with filling materials was dyed with methylene blue solution 31) (Figs. 3a, 4a, 5a, and 6a).It is speculated that there is a pathway around the dyed dentin 32) .…”
Section: Observation Of Sectionsmentioning
confidence: 99%